"Send My Information": Increasing public accessibility to clinical trials by facilitating participant expression of interest. Issue 1 (11th February 2022) - Dunkel, Leah; Byrne, Loretta M.; Olson, Erik; Russell, Michael; Tan, Jason; Phillips, Kaysi; Wilkins, Consuelo H.; Harris, Paul A.
Abstract: Introduction: The process of identifying and connecting with clinical trial study teams can be challenging and difficult for members of the public. The national volunteer community registry, ResearchMatch, and the public clinical trials search tool, Trials Today, work in tandem to bridge this connection by providing a streamlined process for potential participants to identify clinical trials which may be of interest. Methods: Building on the existing infrastructure of ResearchMatch and Trials Today, we created a mechanism by which the public can request that their basic contact information (e.g., email/phone) be securely shared with any actively recruiting clinical trial, including trials with no existing relationship with ResearchMatch. Results: Within the first 2 years of use (July 2019–July 2021), ResearchMatch Volunteers sent 12, 251 requests to study teams. On average, 20% of these requests were accepted by the study teams. Conclusions: The utilization of this tool indicates that there is active interest among members of the public to independently contact study teams about trials of interest. Additionally, research teams unaffiliated with ResearchMatch are willing to at minimum accept contact information. This allows ResearchMatch to successfully serve as a medium, connecting members of the public with actively recruiting trials.